Osteogenin and recombinant bone morphogenetic protein 2B are chemotactic for human monocytes and stimulate transforming growth factor beta 1 mRNA expression. - Cunningham, N S (1992)
Subcutaneous implantation of demineralized bone matrix initiates a sequence of developmental events, which culminate in endochondral bone formation. During early stages of development of matrix-induced implants, ED1, Ia-positive monocytes-macrophages were observed, suggesting that in the initial phases of the endochondral bone formation cascade, the bone-inductive protein osteogenin and related bone morphogenetic proteins (BMPs) might serve as potent chemoattractants to recruit circulating monocytes. In this investigation, we demonstrate that at concentrations of 10-100 fg/ml (0.3-3 fM), native bovine osteogenin and recombinant human BMP-2B (rhBMP-2B) induce the directed migration of human blood monocytes in vitro. This chemotactic response was associated with expression of BMP binding sites (receptors) on monocytes. About 750 receptors per cell were detected with an apparent dissociation constant of 200 pM. Both osteogenin and rhBMP-2B at higher concentrations (0.1-30 ng/ml) stimulated mRNA expression for an additional regulatory molecule, type beta 1 transforming growth factor (TGF-beta 1) in human monocytes. TGF-beta 1, in turn, is known to induce a cascade of events leading to matrix generation. Monocytes stimulated by TGF-beta are known to secrete a number of chemotactic and mitogenic cytokines that recruit endothelial and mesenchymal cells and promote their synthesis of collagen and associated matrix constituents. TGF-beta 1 in concert with these other cytokines and matrix components regulates chemotaxis, mesenchymal proliferation, differentiation, angiogenesis, and controlled synthesis of extracellular matrix. Our results demonstrate that osteogenin and related BMPs through their profound effects on monocyte recruitment and cytokine synthesis may promote additional successive steps in the endochondral bone formation cascade.